FUNCTIONAL ROLE OF THE WATER POLICE IN LAW ENFORCEMENT OF CRIMES THAT OCCUR IN SEA AREAS - Ridwan, Mohammad (Jurnal Hukum Khaira Ummah, 2024)
The purpose of this study is to determine and analyze the working system of the water police in enforcing maritime crime law. In this writing, the author uses a normative legal method with a descriptive analysis research specification. Law enforcement at sea is one of the important national issues, considering that Indonesia's marine resources are very abundant, both in terms of marine aspects, fisheries aspects, and marine-based technological innovation. This oceanic natural background makes the Indonesian nation and state maritime in nature. In addition, Indonesia is geographically strategically located between the intersection of two oceans and two continents, so that Indonesia's sea area is a very important sea lane for world trade routes and national and international shipping traffic. In order to create conditions in Indonesian waters that are safe from the threat of territorial violations, safe from the dangers of shipping navigation, safe from illegal exploitation and exploration of natural resources that are Indonesia's marine potential and environmental pollution, and safe from crimes and violations of the law, both from within the country and from abroad, it is necessary to implement law enforcement in marine areas. In Indonesia, law enforcement officers who have the authority to enforce the law in marine and water areas are in several institutions, one of which is the Water Police or known as POLAIR. In carrying out law enforcement functions at sea.